Light and hormonal regulation of the tomato plastidial development and maintenance gene GOLDEN 2-LIKE 2 and its effect on fruit nutritional quality - Lupi, Alessandra Cavalcanti Duarte (2017)
Plastids are organelles responsible for several essential aspects for plant development, like photosynthesis, nitrogen assimilation and synthesis of several compounds of secondary metabolism. Chloroplasts differentiation and activity are highly regulated by light, and several proteins and mechanisms involved in these processes have been characterized. The GOLDEN 2-LIKE (GLK) transcription factors controls the expression of several genes related to photosynthesis, plastid biogenesis and maintenance. Solanum lycopersicum genome harbors two copies of this gene, SlGLK1 and SlGLK2 and, although they are functionally redundant, their expression pattern is different, once SlGLK1 predominates in leaves, while only SlGLK2 is expressed in fruit, precisely at the pedicel region. During tomato domestication, selection for varieties that ripened evenly resulted in the fixation of uniform ripening mutation (Slglk2) in most cultivated varieties, resulting in alterations in fruit metabolic composition. In this context, the objective of this work was to functionally characterize SlGLK2 gene aiming to understand in which way phytochrome mediated light and phytohormones, particularly auxins and cytokinins, regulates this gene expression, and how SlGLK2 presence affects fruit nutritional quality. To achieve this, a detailed transcriptional profile of SlGLK2 was performed in fruits of wild plants, Slglk2 mutant and plants deficient for light perception or hormonal signaling. The effect of SlGLK2 over nutritional quality was evaluated by characterizing carbon and vitamin E metabolism. Additionally, reporter protein GUS activity was quantified in transgenic plants that express uidA gene under control of promoters responsive to cytokinins or auxins in SlGLK2 or Slglk2 genotypes, to analyze if hormonal activity is affected by SlGLK2 presence. Finally, in order to verify if the presence of SlGLK2 is sufficient to reverse the chlorotic phenotype of the mutant aurea, promoting the differentiation and plastidial maturation even in the absence of functional phytochromes, transgenic lines were generated by overexpressing the SlGLK2 gene on aurea-Slglk2 genetic background. The integrated data analysis allowed us to conclude that the content of soluble sugars and vitamin E correlate with the expression of SlGLK2, that the expression of SlGLK2 is repressed by auxins, that SlGLK2 positively participates in the signaling of cytokinins, and that its overexpression partially reverts the phenotype of the aurea-Slglk2 mutant fruits. The results obtained in this work contributes to a better understanding of the regulatory network that interconnects SlGLK2 gene, phytohormones and light, promoting the plastidial activity and consequently, determining the nutritional quality of the tomato fruit, an important component of the human diet